Design of an improvement plan applying Lean Tools in a baking company. Trujillo, 2024 - Geldres Marchena, Teodoro Alberto; Huamanchumo Cortez, Flavio Cesar Alexis; Núñez Flores, Pamela Cristina (LACCEI, 2024)
The main objective of the project is to develop an improvement plan for the bakery company using industrial engineering tools to reduce operating costs. The company, which specializes in the production of bread, faces several challenges that affect its profitability, such as costs due to spoilage, loss due to non-productive times, costs associated with employee absence due to paid medical leave caused by workplace accidents, over costs for raw materials, costs for unnecessary movements, and costs for disorganization in the warehouse. These problems were quantified, resulting in an annual loss of S/ 45,632. Two solution alternatives were presented, choosing alternative 2, which incorporates tools such as time studies, staff training, 5S methodology, supplier control, and a worker safety and health system (SGSST). After researching engineering standards, a simulation with Monte Carlo and ProModel was conducted, reducing annual losses to S/ 19,541.59, generating a benefit of S/ 26,090.41 and reducing the initial loss by 57.18%. The 12-month economic evaluation confirmed the feasibility and profitability of the proposal, with an NPV of S/ 50,451, an IRR of 44%, and a B/C ratio of S/ 1.50. Additionally, continuous monitoring was planned to ensure the effective implementation of the improvements and key performance indicators were defined to monitor progress.